Portfolio diversification during the COVID-19 pandemic: Do vaccinations matter? - Pham, Son Duy; Nguyen, Thao Thac Thanh; Do, Hung Xuan; Vo, Xuan Vinh (Journal of Financial Stability, 2023)
The COVID-19 vaccine rollout expects to mitigate the severe negative impacts of the pandemic on global financial markets. Our study provides supporting evidence for this expectation. We find robust evidence that vaccinations significantly reduce the cross-country stock volatility connectedness among G7 nations, suggesting that the diversification benefits of an international equity portfolio may be enhanced during the pandemic when vaccinations accelerate. We present two explanations for this result. First, the vaccine deployment improves stock market return and decreases individual stock market volatility. Second, the vaccine rollout helps a country’s stock market be more resilient to exogenous shocks. We further demonstrate that a global portfolio using a tactical allocation rule based on the intensity of vaccinations can outperform a buy-and-hold portfolio in terms of risk-adjusted returns.